PENGARUH KOMBINASI PAKAN ALAMI DENGAN PAKAN BUATAN TERHADAP PERTUMBUHAN BENIH IKAN LELE DUMBO (Clarias gariepinus) The Influence of Combination Natural Feed with Artificial Feed for Growth the African Catfish (Clarias gariepinus) - Ricky Amanta; Syammaun Usman; M. Riza Kurnia Lubis (AQUACOASTMARINE, 2015)
Increased cultivation of the African catfish, the demand for seedling in the form of seed is also increasing. Therefore, It has to have an availability seeds with good quality and quantity in halls seeding. Giving proper woof can determine the quality and continuity of the fish seed. Increasing growth of the African catfish by giving the combination feed. The purpose of this study was to determine the effect of the use combined natural feed of dried sludge worms (Tubifex sp.) with artificial feed of pellets flour to the seed growth of the African catfish (Clarias gariepinus), it sizes 3,32 – 3,40 cm with a weight is 0,37 – 0,38 g were kept in the aquarium measuring 60 × 30 × 30 cm by 15 units with a volume is 20 liters per aquarium and arranged randomly. The design used was a completely randomized design (CRD) with a combination of 100 % pellets flour, 100 % dried sludge worms, 75 % pellets flour + 25 % dried sludge worms, 50 % pellets flour + 50 % dried sludge worms, 25 % pelets flour + 75 % dried sludge worms. Feed given as much as 10 % of the body weight of the fish. The results showed that the good combination for the African catfish growth is 75 % pellets flour + 25 % dried sludge worms, with length and weight growth is 3,51 cm and 1,66 g.Keywords: Clarias gariepinus, Feed, Combination, Growth